Group Leasing Approach to Sustain Farming and Rural Livelihoods : The Journey of Women Farmers in Kudumbashree Kerala - World Bank (Washington, DC : World Bank, 2022)
Kudumbashree is a society designed and established in 1997 by the State Poverty Eradication Mission (SPEM) of the government of Kerala (GoK) with a broad objective to eradicate poverty and empower women through community-based organizations that operate under the umbrella authority of local government institution. The program aims to empower women’s groups and make them the focal point of sustained socio-economic development. Besides income generation activities and microcredit, the women’s groups work on health, nutrition, agriculture and other related development activities. Since its inception, Kudumbashree has been identified by the state government as the nodal agency for all the state and central government schemes that target the socially and economically weaker sections of the society. Women enter the programme as cultivators as opposed to agricultural labourers and have control over the means of production and access to formal credit to help increase the returns from farming. Activities under this initiative include selection of beneficiaries into Neighborhood Groups (NHG), clustering them into joint liability groups (JLGs), identification of available land and support to negotiate informal leases, training, distribution of inputs and release of eligible agricultural entitlements managed by Kudumbashree. The identified beneficiaries are collectivized as JLG to undertake agriculture. Agriculture incentives are provided to the JLGs based on the crop types. Interest subsidies on agriculture bank loans are also provided to the JLGs by Kudumbashree through various Central and State agriculture schemes.